CONTROLLED DELIVERY OF ANTIRETROVIRAL DRUG-LOADED CROSS-LINKED MICROSPHERES BY IONIC GELATION METHOD - S, PRINCELY; Basha N, Saleem; S, Nandhakumar; Md, Dhanaraju (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: Lamivudine (LVD) is a nucleoside reverse transcriptase inhibitor originally developed as an antiretroviral drug and primarily used in the treatment of most common chronic disease of the planet, acquired immune deficiency syndrome and hepatitis B. The main objective of the study is to develop controlled drug delivery system to increase the efficacy of antiretroviral drug, LVD against human immunodeficiency virus infections. Methods: The microencapsulation of LVD in gelatin microspheres was carried out by cross-linking process with glutaraldehyde saturated toluene using ionic-gelation method. The prepared microspheres were evaluated for particle size analysis, % yield value, % drug content, drug entrapment efficiency, scanning electron microscopy for surface morphology, swelling index, accelerated stability studies, Fourier transform infrared radiation spectroscopy (FT-IR) and differential scanning calorimetry (DSC) for polymer drug compatibility, in vitro dissolution efficiency and release kinetic studies. Results: The obtained microspheres showed very smooth surface and exhibited regular spherical geometry due to higher crosslinking density. FT-IR and DSC revealed the absence of drug polymer interactions. The percentage yield, entrapment efficiency and drug content for F6 LVD microspheres was found to be 79.31%, 65.55% and 96.25% respectively. The particle size was ranged from 34.61% to 51.45 Î¼m sizes and in vitro release profile showed that cross-linking density of gelatin microspheres effectively controlled the release of LVD. Conclusion: The findings of our investigation demonstrated that F6 of gelatin-LVD microspheres had good controlled release profile with maximum entrapment efficiency and prolonged drug release for 24 hrs or longer and this formulation would be capable of overcoming the drawbacks and limitations of LVD conventional dosage forms. Keywords: Lamivudine, Microspheres, Controlled release, Gelatin, Fourier transform infrared, Differential scanning calorimetry, In vitro release kinetics.